Introducing narratives in Europeana: A case study - Meghini, Carlo; Bartalesi, Valentina; Metilli, Daniele; Benedetti, Filippo (Zielona Góra: Uniwersytet Zielonogórski)
We present a preliminary study to introduce narratives as a first-class functionality in digital libraries. The general idea is to enrich those libraries with semantic networks of events providing a meaningful contextualisation of the digital libraries` objects. More specific motivations are presented through a set of use cases by different actors who would benefit from using narratives for different purposes. Then, we consider a specific digital library, Europeana, the largest European digital library in the cultural heritage domain.
Keywords: digital libraries; narratives; Europeana; ontologies